Veiled Truths: Iranian Women and Risky Sexual Behavior in the Context of Substance Use - E Merghati Khoei; M Jamshidimanesh; MH Emamian; F Sheikhan; K Dolan; K Brady (JRI, 2018)
Background: Substance use disorders and risky sexual behavior coexist for some women. Explanatory models of women's sexuality in the context of substance use are under study. This study aimed to explore how women’s sexual behavior can become risky in the context of substance use. Methods: In this ethnographic inquiry, 25 women with substance use disorders (SUDs) were included at two Drop-In-Centers (DICs) in South Tehran. Observation, semi-structured interviews and field notes were used to collect data. Qualitative content analysis was used to attain the explanatory model of women’s sexual behaviors in the context of substance use. Results: Three major themes emerged from the data analysis regarding their lives in the context of substance use; 1) life in the context of drug abuse, 2) negative self-perception, and 3) strive to survive. Subthemes were identified as loss of contact with family, social stigma, self-forgetfulness, worthlessness, low self-efficacy, and unsafe sexual context. Conclusion: Findings suggest that women with SUDs are highly interwoven with women’s sexual health, facilitating a shift towards risky behaviors. Integration of safe sexual skills building programs with substance use treatment is needed.